2014
DOI: 10.4028/www.scientific.net/kem.611-612.1710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anisotropic Yield Criterion Parameters from a Single Biaxial Tensile Test

Abstract: The present work deals with the calibration strategy of yield functions used to describe the plastic anisotropic behavior of metallic sheets. In this paper, Bron and Besson yield criterion is used to model the plastic anisotropic behavior of AA5086 sheets. This yield model is flexible enough since the anisotropy is represented by 12 parameters (4 isotropic parameters and 8 anisotropic parameters in plane stress condition) in the form of two linear fourth order transformation tensors. The parameters of this ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This issue has been addressed by Martins et al [39] who studied the influence of different cruciform specimen geometries on the hardening and plastic anisotropy parameters. They found that VFM-based identification with specimen geometry proposed by Zhang et al [40,41] yields a higher error on the shear parameter N in the Hill48 model in comparison to the other two proposed geometries and also with respect to other Hill's parameters. A similar study was also conducted by Schmaltz and Willner [42], who tested even more sophisticated cruciform specimen designs.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…This issue has been addressed by Martins et al [39] who studied the influence of different cruciform specimen geometries on the hardening and plastic anisotropy parameters. They found that VFM-based identification with specimen geometry proposed by Zhang et al [40,41] yields a higher error on the shear parameter N in the Hill48 model in comparison to the other two proposed geometries and also with respect to other Hill's parameters. A similar study was also conducted by Schmaltz and Willner [42], who tested even more sophisticated cruciform specimen designs.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Both materials were characterized in previous works in uniaxial tension [35,44], and their mechanical properties are given in The specimen is settled in the center of the machine. It is connected to the load cell via a bi-articulated link (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The main aim is to reduce the strain in the arms and to increase the strain in the central area, and in some case to promote rupture in the central area, e.g. [35] for a survey of the different proposed geometries.…”
Section: Introductionmentioning
confidence: 99%